1999
DOI: 10.1016/s0194-5998(99)80108-9
|View full text |Cite
|
Sign up to set email alerts
|

EMS1 gene amplification correlates with poor prognosis in HNSCC

Abstract: Conclusion: FISH is an ideal technique for analysis of chromosomal aberrations in paraffin-embedded, archival tissue specimens. While chromosome 20Q amplification has been suggested as a possible mediator of tumorigenesis in head and neck cancers, using FISH, we have shown no direct evidence of either amplification or deletion of the specific region 20q13 in head and neck squamous carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
130
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(141 citation statements)
references
References 0 publications
10
130
0
1
Order By: Relevance
“…Amplification of the CTTN gene has been linked to poor prognosis in HNSCC (Rodrigo et al, 2000), yet the relationship between cortactin protein levels and prognosis has not been thoroughly investigated to date. Tissue microarrays have previously been shown to represent reliable tools for the identification of cellular and molecular alterations in several tumour types, including HNSCCs (Gomaa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of the CTTN gene has been linked to poor prognosis in HNSCC (Rodrigo et al, 2000), yet the relationship between cortactin protein levels and prognosis has not been thoroughly investigated to date. Tissue microarrays have previously been shown to represent reliable tools for the identification of cellular and molecular alterations in several tumour types, including HNSCCs (Gomaa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the poor survival subgroup, we also observed at chromosome 11q13 two areas of gain marked by CCND1, FGF3, and EMS1 genes. Interestingly, all these genes have been associated with different tumors; [16][17][18] in particular, EMS1 amplification and overexpression was related to poor prognosis in breast cancer 19 and disease progression in esophageal squamous cell carcinoma. 20 A DNA gain at chromosome 20q is the most frequent chromosomal aberration described in esophageal adenocarcinoma, being found in up to 60% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the total number of chromosomal imbalances was correlated to patient survival, a significant association (P ¼ 0.002) between the total number of gains/losses and survival was found. In particular, by dividing the patients according to their median survival time (20 months), we found that the mean number of quantitatively altered genes per tumor was 20.7 (range 6-33) in patients with a survival r20 months (17 patients), compared to 10.1 (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] in patients with a survival 420 months (16 patients) ( Table 2). Similarly, stratification of the patients according to the median number of chromosomal imbalances (12 aberrations), showed a good association with survival (P ¼ 0.014).…”
Section: Association Between Copy Number Alterations and Survival In mentioning
confidence: 99%
“…Several studies report that patients with HPV-positive head and neck tumours have an improved prognosis (Ritchie et al, 2003;Schlecht, 2005), whereas amplification of 11q13 has been associated with a more rapid and frequent recurrence of disease (Fujii et al, 2001) and poorer survival (Akervall et al, 1997;Rodrigo et al, 2000;Namazie et al, 2002). Weinberger et al (2006) has shown that patients with HPV-positive tumours which express high levels of p16 protein and low levels of p53 protein present with a favourable prognosis.…”
Section: Discussionmentioning
confidence: 99%